The Impact of COVID-19 Pandemic on Final Year Medical Students: Single Center Study - Ahmad Ussaid, Farwa Pervaiz, Wajid Ali Rafai, Faisal Amin Baig, Sarwat Hassan Syed, Ahsan Masud (Journal of Rawalpindi Medical College, 2021)
Introduction: The COVID-19 health emergency led to adoption of unprecedented measures that have never been seen in recent times. The study examines the effect of COVID-19 on final year medical students’ final professional examination preparedness, transition to house job and earlier assistantship. Methodology: This descriptive cross-sectional survey was conducted in September – October 2020 after institutional review board approval at University College of Medicine and Dentistry (UCMD) in Lahore, Pakistan. A total of 112 final year medical students responded to this survey whereas 13 did not. Data was analyzed using SPSS 25. Chi square test was applied to evaluate the impact of COVID 19 on variables of interest (p-value< 0.05 considered significant). Results: Postponement of clinical rotations, written exams, OSPEs and clinical ward tests was reported by 62%, 78%, 71% and 48% students respectively whilst 29%, 13%, 18% and 21% students respectively stated it to be formatted. A statistically significant impact (p<0.05) was observed for final professional examinations preparedness and confidence to assist earlier. Conclusion: The study demonstrated the significant impact of COVID-19 on final year medical students’ examination preparedness and confidence to assist earlier in hospital. Improvised teaching methodology is urgently needed to fill in the lapses in their education. Keywords: COVID-19, Medical Education, Final year MBBS professional examination, OSPE, Earlier Assistantship, House Job.